2006
DOI: 10.1152/japplphysiol.00012.2006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between local perfusion and FFA uptake in human skeletal muscle—no effect of increased physical activity and aerobic fitness

Abstract: We investigated heredity-independent effects of increased physical activity and aerobic fitness on skeletal muscle free fatty acid (FFA) uptake, perfusion, and their heterogeneity at rest and during exercise. Also, the relationship between local skeletal muscle FFA uptake and perfusion was studied. Nine young adult male monozygotic twin pairs with significant difference in physical activity [229 min (SD 156) average time spent for conditioning exercise per week in more and 98 min (SD 71) in less active twins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Hannukainen et al (2006) demonstrated that perfusion and FFA uptake levels were higher in the VI muscle than in the other three synergists (Hannukainen et al, 2006). Since intracellular metabolism or membrane potential could be strongly related to blood flow behavior (Moritani et al, 1992;Sjøgaard et al, 1988), variance in surface EMG signal response during sustained contraction among the four muscles of the QF muscle group could be reflected in different blood flows among individual muscle components.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Hannukainen et al (2006) demonstrated that perfusion and FFA uptake levels were higher in the VI muscle than in the other three synergists (Hannukainen et al, 2006). Since intracellular metabolism or membrane potential could be strongly related to blood flow behavior (Moritani et al, 1992;Sjøgaard et al, 1988), variance in surface EMG signal response during sustained contraction among the four muscles of the QF muscle group could be reflected in different blood flows among individual muscle components.…”
Section: Discussionmentioning
confidence: 97%
“…Neuromuscular activation of all four components of the QF muscle group has thus not been covered using surface EMG techniques in previous studies. However, the importance and specificity of the VI muscle in force generation during knee extension has been reported (Blazevich et al, 2006;Hannukainen et al, 2006;Lieb and Perry, 1968;Zhang et al, 2003). It was estimated that the contribution of the VI muscle was up to 50% of electrical stimulation-evoked knee extension torque during submaximal isometric contraction (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects completed a maximum oxygen uptake (VO2 max) test, electrocardiography and echocardiography studies. Positron Emission Tomography (PET) imaging studies of liver and muscle metabolism were conducted during an exercise protocol (Hannukainen et al, 2006).…”
Section: Co-twin Control Studiesmentioning
confidence: 99%